THE INFLUENCE OF INDONESIAN CELEBRITY BRAND AMBASSADOR ON CONSUMER BUYING BEHAVIOR OF FEMALE BEAUTY PRODUCTS - Bachrun, Anggreyni (Sam Ratulangi University, 2015)
ABSTRACT Celebrity brand ambassador has become popular in Indonesia. Many companies advertise their brand has used celebrity brand ambassador to attract people to buy their product. This study aims to find out the influence of Indonesian celebrity brand ambassador on consumer buying behavior of female beauty products. The method used to analyze the data is the Simple Regression Analysis which enables the researcher to analyze the influence of the independent variable, which is Brand Ambasador to the dependent variable, which is Consumer Buying Behavior. The independent variable in this research is Indonesian Celebrity Brand Ambassador. 100 female under age between 17 to 50 years were surveyed as respondents. Data have been collected from both the primary and secondary source. For the primary researcher has used questionnaire. The result of this research shows that there is significant simultaneous and partial influence of Indonesian celebrity brand ambassador on consumer buying behavior of beauty products. Keywords: Celebrity Brand Ambassadors, Consumer Buying Behavior.